Enzymatic potential for the valorization of agro-industrial by-products - Barcelos, M.C.S; Ramos, C.L.; Kuddus, M.; Rodriguez-Couto, S.; Srivastava, N.; Ramteke, P.W.; Mishra, P.K.; Molina, G. (Springer, 2020)
Agro-industrial residues and by-products are a crescent environmental problem since they are often discarded without proper treatment, and still have growing production. These residues are rich from a nutritional point of view and contain various industrial relevant compounds, such as phenolic compounds, fibers, vitamins, sugars and others. The crescent worrying about environmental issues has led researchers and industries to focus on “eco-friendly” solutions for everyday problems. In this sense, the use of enzymes for the valorization of agro-industrial residues is a safe and green alternative technology. Hence, this review aims to show the enzyme potential for the use and valorization of several agro-industrial residues, focusing on the most produced residues worldwide, such as fruits, grains and lignocellulosic residues, as well as a brief explanation of microbial enzymes, its production and optimization, altogether with tools to identify producing microorganisms. © 2020, Springer Nature B.V.
Keywords: Enzymes; Enzymatic extraction; Fruit residues; Grains residues